CPM 1. Performance of Lowland Red Rice (Oryza sativa L.) as Influenced by Combined Application of Organic and Inorganic Fertilizers (2018)
This study was conducted to evaluate the effects of combined application of organic and inorganic fertilizers on the agronomic, and yield and yield performance of lowland red rice; determined the fertilizer combination that will produce the highest grain yield of lowland red rice; and assess the economic profitability of lowland red rice production to integrated nutrient management strategy adopted. This was laid out in a RCBD with three replications. The different treatments were mainly based on the combined application of organic and inorganic fertilizers and compared these with unfertilized control. Fertilized plants significantly affected almost all agronomic characteristics, and the yield and yield components such as the number of productive tillers, number of unfilled grains panicle-1and grain yield. Plants applied with 2.5 t ha-1 IMO6+ 2.5 t ha-1 vermicompost + 90-45-45 kg ha-1 N, P2O5, K2O(T6) produced significantly taller plants comparable to T5 and T2, and apparently obtained higher grain yield of 4.16 t ha-1 than that of unfertilized control with only 2.98 t ha-1. among the fertilized plants, higher net income of Php 34, 981.00 ha-1 was achieved in plants that received inorganic fertilizer at recommended level (T1). Rice plants applied with combined application of organic and inorganic fertilizers (T6) obtained the highest gross income of Php 83,200.00. Due to high production cost of the said treatment, this gave lower net income of 9,665.00 ha-1. for recommendation purposes however, T6 is highly recommended if growers have their own production for organic fertilizer for lowland red rice cultivation.